Transient Free Convection Flow of an Elastico-Viscous Fluid Past an Infinite Vertical Plate - R. Deka; U.N. Das; V.M. Soundalgekar (Engineering Transactions, 1995)
A solution to the problem of an unsteady, non-isothermal flow of an elastico-viscous fluid in a half-space is presented. The flow is induced by a temperature jump on the limiting plane. The constitutive equations of Walters' liquid B' are used.